Evaluasi Kualitas Pelayanan dan Dampaknya Terhadap Kepuasan Nasabah di PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Bengo, Cabang Watampone - Samsul Rizal; Abdul Rahman Rahim; Eka Wardiana (Jurnal Ilmu Manajemen Profitability, 2020)
The purpose of this study was to evaluate the quality of service and its impact on customer satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk. Bengo Unit, Watampone Branch. This study covered all customers met at the location, with a total population of 500 customers. The sample used in this study was 84 respondents, selected using incidental sampling techniques. Data were collected through descriptive statistical techniques, simple linear regression analysis, and hypothesis testing. The results of the analysis showed a t count of 7.669, while the t table was 1.98932, indicating that service quality has a positive effect on customer satisfaction. Analysis with SPSS produced a value of R = 0.646 and R² = 0.418 or 41.8%, which means that 41.8% of the variability in customer satisfaction can be explained by service quality. Meanwhile, 58.2% of customer satisfaction cannot be explained by the variables studied.